2019
DOI: 10.1016/j.devcel.2019.07.025
|View full text |Cite
|
Sign up to set email alerts
|

Germ Granules Coordinate RNA-Based Epigenetic Inheritance Pathways

Abstract: Highlights d Disrupting germ granules leads to aberrant levels of endogenous small RNAs d Aberrantly expressed small RNAs misregulate germline gene expression d Gene expression defects caused by germ granule loss are inherited across generations

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(52 citation statements)
references
References 60 publications
0
49
0
Order By: Relevance
“…They are crucial for fertility and totipotency 8 , and some of their components can display liquid droplet behavior 9 ,– 12 . In the primordial germ cells of the embryo, P granules are proposed to protect mRNAs from small RNA-based regulatory pathways 13 , 14 , and to localize and concentrate mRNAs for robust germline development independent of translational repression 15 , 16 . In adult germ cells, P granules are essential for proper germ cell development 17 , 18 .…”
Section: Introductionmentioning
confidence: 99%
“…They are crucial for fertility and totipotency 8 , and some of their components can display liquid droplet behavior 9 ,– 12 . In the primordial germ cells of the embryo, P granules are proposed to protect mRNAs from small RNA-based regulatory pathways 13 , 14 , and to localize and concentrate mRNAs for robust germline development independent of translational repression 15 , 16 . In adult germ cells, P granules are essential for proper germ cell development 17 , 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Germ granules coordinate germ cell mRNA regulation with piRNA inheritance through the role of PIWI proteins in both processes. Recent studies in C. elegans have shown that piRNA/PRG1-dependent mRNA accumulation in germ granules prevent their silencing, strengthening the function of piRNAs in germ granules for mRNA storage and surveillance (56,57). In Drosophila, Aub mediates the link between piRNAs and mRNA regulation in germ granules since Aub localization to germ granules depends on its loading with piRNAs (12) and Aub/piRNAs play a general role in the localization and stabilization of germ cell mRNAs in germ granules (13,19).…”
Section: Discussionmentioning
confidence: 99%
“…The RdRPs that produce the amplified siRNAs, EGO-1 and RRF-1, are localized in the germ granules ( Claycomb et al., 2009 ; Phillips et al., 2012 ). In addition, mutants lacking core germ granule components misexpress different populations of amplified siRNAs ( Dodson and Kennedy, 2019 ; Lev et al., 2019b ; Ouyang et al., 2019 ; Suen et al., 2020 ) (discussed further below). Additionally, a Z granule component, the helicase-domain protein ZNFX-1, contributes to the alignment pattern of amplified small RNAs aligning along the targeted gene.…”
Section: Amplification Of Small Rnas In Germ Granulesmentioning
confidence: 99%
“…In the recent decade regulatory small RNAs were implicated in the transmission of various phenotypes in worms ( Ewe et al., 2020 ; Gammon et al., 2017 ; Moore et al., 2019 ; Rechavi et al, 2011 , 2014 ), flies ( Casier et al., 2019 ; Hermant et al., 2015 ), plants ( Ito et al, 2011 , 2016 ; Liu et al., 2019 ; Zhong et al., 2013 ), and mice ( Chen et al., 2016 ; Conine et al., 2018 ; Gapp et al., 2014 ; Grandjean et al., 2015 ; Rodgers et al., 2015 ; Zhang et al., 2018b ). Notably, transgenerationally heritable small RNAs seem to differ from DNA-based genetics: their inheritance obeys a different set of rules ( Houri-Ze'evi et al., 2016 ; Houri-Zeevi et al., 2020 ), their biogenesis can be induced in response to the environment ( Ni et al., 2016 ; Rechavi et al, 2011 , 2014 ), and their cellular pools change across generations in a continuous (rather than discrete) manner that seems to dilute ( Vastenhouw et al, 2003 ; Alcazar et al., 2008 ; Houri-Ze'evi et al., 2016 ) or concentrate ( Dodson and Kennedy, 2019 ; Houri-Ze'evi et al., 2016 ; Lev et al., 2017 ; 2019b ; Ouyang et al., 2019 ; Simon et al., 2014 ). This review covers the role of the germ granules in regulating transgenerational small RNA responses and focuses on knowledge gained from studies in the nematode Caenorhabditis elegans, which plays an instrumental role ( Perez and Lehner, 2019 ) in uncovering the principles and rules of transgenerational epigenetic inheritance.…”
Section: Introductionmentioning
confidence: 99%